Immuno-Thrombotic Complications of COVID-19: Implications for Timing of Surgery and Anticoagulation - Bunch, Connor M.; Moore, Ernest E.; Moore, Hunter B.; Neal, Matthew D.; Thomas, Anthony V.; Zackariya, Nuha; Zhao, Jonathan; Zackariya, Sufyan; Brenner, Toby J.; Berquist, Margaret; Buckner, Hallie; Wiarda, Grant; et al. (Frontiers in Surgery, 2022)
Early in the coronavirus disease 2019 (COVID-19) pandemic, global governing bodies prioritized transmissibility-based precautions as the foundation for delay of elective procedures. As elective surgical volumes increased, patients faced increased postoperative morbidity and mortality, and clinicians had limited evidence for stratifying individual risk in this population recovering from acute and convalescent COVID-19. Here, the most recent recommendations by the American Society of Anesthesiologists and leading surgical societies are summarized, including the guidelines for general surgery, neurosurgery, cardiothoracic, vascular, obstetrics, orthopaedics, oculoplastic and plastic surgery. For some of the aforementioned surgical subspecialties, Elective Surgery Acuity Scales are provided. We also outline a framework for stratifying the individual COVID-19 patient’s fitness for surgery based on the symptoms and severity of acute or convalescent COVID-19 illness, biomarker assessment of coagulopathy, and acuity of the surgical procedure. Although the most common manifestation of SARS-CoV-2 is COVID-19 pneumonitis, every system in the body is potentially afflicted by the endotheliitis. This endothelial derangement most often manifests as a hypercoagulable state on admission with associated occult and symptomatic venous and arterial thromboembolisms. The delicate balance between hyper and hypocoagulable states is defined by the local immune-thrombotic crosstalk that results commonly in a hemostatic derangement known as fibrinolytic shutdown. In tandem, the hemostatic derangements that occur during acute COVID-19 infection affect not only the timing of surgical procedures, but also the incidence of postoperative hemostatic complications related to CAC. Traditional methods of thromboprophylaxis and treatment of arterial and venous thromboses after surgery require a tailored approach guided by an understanding of the pathophysiologic underpinnings of the COVID-19 patient. Likewise, a prolonged period of risk for developing hemostatic complications following hospitalization due to COVID-19 has resulted in guidelines from differing societies that recommend varying periods of delay following SARS-CoV-2 infection. In conclusion, we propose the perioperative, personalized assessment of COVID-19 patients’ CAC using viscoelastic hemostatic assays and fluorescent microclot analysis.